Development Of Interpersonal Relationships in Global Virtual Teams - Aleem, Majid (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
This study investigates the development of relationships in same global virtual team working on different projects. The purpose is to explore how do interpersonal relationships develop in terms of characteristics of virtuality and if there is any influence of project lifespan on the development of these relationships. Since relationships are dynamic in nature and are influenced by multiple levels of variables including individual, group and organizational level, therefore characteristics of virtuality have been considered from all these aspects so as to study their influence on development of relationships. In this study, relationships have been studied at two different levels. At first, dyadic relationships between two members of a GVT have been analyzed and thereafter, focus has been on the development of relationships among the team, based on these dyads. Characteristics having influence on development of relationships include trust, physical distance, time zone difference, cultural and language differences, level of formalization in the organization and means of communication used by team members. Level of formalization and means of communication are two characteristics which emerged after empirical study and are found to have direct influence on development of relationships. Remaining characteristics have been identified through literature review. In order to conduct the study, qualitative methodology has been applied. Empirical data has been collected based on a single case study while using semi-structured interviews as data gathering technique. Data analysis has been performed by applying thematic analysis along with the utilization of company documents such as work sheets, minutes of meetings and recordings of conferences. Findings of the study indicate that development of relationships, both at dyadic level and team level, is influenced by different events taking place among different members of GVT. These events have either positive or negative influence on the characteristics of virtuality, which leads to development of the relationships. It has been found that, trust, among all factors plays a greater role in development of these relations. Contrary to the belief that most conflicts arise among members of different cultures, they are equally likely to happen among the members from same culture in GVT environment. Study suggests that relationship development is not a smooth process but it fluctuates based on different events in teams. For further research, teams within large firms shall be studied along these lines. This study is an early attempt towards bringing different characteristics of virtuality together which previously, have been studied individually. It is therefore plausible to conduct similar studies so as to generalize the findings of this study which has provided a starting point.